The simulation of granular attachment on the porous vertical surfaces. Issue 1 (April 2021) - Muliyati, D; Sumardani, D; Siswoyo, S; Viridi, S; Bakri, F; Handoko, E; Permana, H
Abstract: Granular simulations have been carried out to visualize attached to porous vertical surfaces. We simulate the optimal ratio of dry surfaces. This simulation uses the uFlex particle with three pore sizes. The movement particle using parabolic motion with the initial horizontal speed only. The simulation results show that for uniform particle velocities, the number of particles that are attached depends on the size of the particle sphere itself. These results can combine with the previous study to use in future research.